A Safety and Efficacy Study of Medium-Dose Etoposide, Cyclophosphamide and Total Body Irradiation Conditioning Before Allogeneic Stem Cell Transplantation for Acute Lymphoblastic Leukemia. Issue 2 (March 2015) - Shigematsu, Akio; Ozawa, Yukiyasu; Onizuka, Makoto; Fujisawa, Shin; Suzuki, Ritsuro; Atsuta, Yoshiko; Hatanaka, Kazuo; Masuko, Masayoshi; Ito, Toshiro; Kobayashi, Naoki; Kato, Jun; Miyamura, Koichi; et al.
Abstract : Background: Prognosis for adult patients with acute lymphoblastic leukemia (ALL) has been reported to be approximately 35% to 50%, even after allogeneic stem cell transplantation (allo-SCT). We previously reported retrospective analyses of a conditioning regimen of medium-dose etoposide, cyclophosphamide (CY), and total body irradiation (TBI) before allo-SCT for ALL. To prospectively analyze the efficacy of this conditioning regimen, we conducted a trial prospectively. Methods: The eligibility criteria of this study were as follows: diagnosis of ALL, aged between 15 and 50 years, in complete remission, and first SCT from HLA serologically matched donor. The primary endpoint of this study was event-free survival at 1 year after SCT, and the events were defined as death and relapse. Results: Fifty eligible patients were treated, and the median age of the patients was 33.5 years. Nineteen patients were Philadelphia chromosome-positive, and 47 were in first complete remission at SCT. All patients achieved neutrophil engraftment. Grade 3 to 4 acute graft-versus-host disease and extensive chronic graft-versus-host disease developed in 4 patients and 18 patients, respectively. No patient died within 100 days after SCT. One-year event-free survival was 76.0%, and 1-year overall survival was 80.0%. The cumulative incidences of relapse and non-relapse mortality at 1-year after SCT were 10.0% and 14.0%, respectively. Conclusions: Medium-dose etoposide + CY + TBI is an effective conditioning before allo-SCT for adult patients with ALL, enabling good disease control without an increase in nonrelapse mortality. A phase 3 trial comparing this regimen with the standard CY + TBI regimen for adult patients with ALL is warranted.